An essential role of adenosine deaminase acting on RNA 1 in coeliac disease mucosa - Di Fusco, Davide; Segreto, Maria Teresa; Iannucci, Andrea; Maresca, Claudia; Franzè, Eleonora; Di Maggio, Giulia; Di Grazia, Antonio; Boccanera, Siro; Laudisi, Federica; Marafini, Irene; Paoluzi, Omero Alessandro; Michienzi, Alessandro; et al. (Frontiers in Immunology, 2023)
Background and Aim: It is well known that type-I interferons (IFNs) are highly expressed in celiac disease (CD) gut mucosa and promote inflammation triggered by gluten ingestion, but the mechanisms that sustain the production of these inflammatory molecules are not well understood. Adenosine deaminase acting on RNA 1 (ADAR1), an RNA-editing enzyme, plays a key role in preventing self or viral RNAs from triggering autoinflammatory responses, most notably within the type-I IFN production pathway. The aim of this study was to evaluate if ADAR1 could contribute to the induction and/or progression of gut inflammation in celiac disease patients. Material and Methods: Expression of ADAR1 was evaluated by duodenal biopsy taken from inactive and active celiac disease (CD) patients and normal controls (CTR) by Real time PCR and Western blotting. To verify the role of ADAR1 in gut inflammation, ADAR1 was silenced in lamina propria mononuclear cells (LPMC) isolated from treated CD with a specific antisense oligonucleotide (AS) and then stimulated with a synthetic analogue of viral dsRNA (poly I:C). IFN-inducing pathways (IRF3, IRF7) in these cells were evaluated with Western blotting and inflammatory cytokines were evaluated with flow cytometry. Finally, the role of ADAR1 was evaluated in a mouse model of poly I:C-driven small intestine atrophy. Results: Reduced expression of ADAR1 was seen in duodenal biopsies of active CD in comparison to inactive CD and normal controls. The addition of a peptic-tryptic digest of gliadin to ex-vivo organ cultures of duodenal biopsies taken from inactive CD patients reduced ADAR1 expression. ADAR1 silencing in LPMC stimulated with a synthetic analogue of viral dsRNA strongly increased the expression of the activated forms of IRF3 and IRF7 and the production of type-I IFN, TNF- and IFN-. Administration of ADAR1 antisense but not sense oligonucleotide to mice with poly I:C-induced intestinal atrophy, significantly increased gut damage and inflammatory cytokines production. Conclusions: These findings show that ADAR1 is an important regulator of gut immune homeostasis and demonstrate that defective ADAR1 expression could contribute to amplifying pathogenic responses in CD gut mucosa.